2010
DOI: 10.2337/dc10-0345
|View full text |Cite
|
Sign up to set email alerts
|

Urine Proteome Analysis May Allow Noninvasive Differential Diagnosis of Diabetic Nephropathy

Abstract: OBJECTIVEChronic renal insufficiency and/or proteinuria in type 2 diabetes may stem from chronic renal diseases (CKD) other than classic diabetic nephropathy in more than one-third of patients. We interrogated urine proteomic profiles generated by surface-enhanced laser desorption/ionization-time of flight/mass spectrometry with the aim of isolating a set of biomarkers able to reliably identify biopsy-proven diabetic nephropathy and to establish a stringent correlation with the different patterns of renal inju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(63 citation statements)
references
References 19 publications
3
56
0
4
Order By: Relevance
“…It remains, however, most likely that some of the patients included in the biomarker studies were unrightfully given the diagnosis of diabetic nephropathy, and it is uncertain how important this contamination of the data is for the study outcomes. Only one marker study in 2010 was found that did incorporate renal biopsy findings and interestingly, in this study, a classification model was able to reliably differentiate diabetic nephropathy from nondiabetic chronic kidney disease (Papale M 2010). Among the best predictors of this classification model were ubiquitin and b 2-microglobulin.…”
Section: Biomarker Studiesmentioning
confidence: 88%
“…It remains, however, most likely that some of the patients included in the biomarker studies were unrightfully given the diagnosis of diabetic nephropathy, and it is uncertain how important this contamination of the data is for the study outcomes. Only one marker study in 2010 was found that did incorporate renal biopsy findings and interestingly, in this study, a classification model was able to reliably differentiate diabetic nephropathy from nondiabetic chronic kidney disease (Papale M 2010). Among the best predictors of this classification model were ubiquitin and b 2-microglobulin.…”
Section: Biomarker Studiesmentioning
confidence: 88%
“…Urine samples were treated as described (17,21). All processed samples were stored at 280°C until use.…”
Section: Sample Collectionmentioning
confidence: 99%
“…Only the peaks in the mass range from 3000 to 30,000 m/z with a signal-to-noise ratio greater than four were used for the data analysis. The reproducibility of SELDI analysis was assessed as previously described (17,21).…”
Section: Sample Collectionmentioning
confidence: 99%
See 2 more Smart Citations